1989
DOI: 10.1002/bip.360280111
|View full text |Cite
|
Sign up to set email alerts
|

Selective agonists for receptors of substance P and related neurokinins

Abstract: Neurokinins and their receptors are a complex system consisting of at least three endogenous agents--substance P (SP), neurokinin A (NKA), and neurokinin B (NKB)--and their corresponding receptor types, respectively, NK-1, NK-2, and NK-3. Investigations on receptors have been made using sensitive and fairly selective pharmacological preparations (the dog carotid artery for the NK-1, the rabbit pulmonary artery devoid of endothelium for the NK-2, and the rat portal vein for the NK-3 receptor), and some natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
(2 reference statements)
3
13
0
Order By: Relevance
“…[1251]NKA binding was displaced by NKA with an IC50 of 12.6 ± 1.6 nM (n = 3) and by naturally occurring neurokinins with the relative rank order of affinity NKA>NKB>SP (Figure 1). This rank order of displacement is consistent with radioligand binding to the NK-2 receptor subtype (Grandordy et al, 1988;Regoli et al, 1989 at 10-6 M stimulated a rapid 4.6 ± 0.6-fold (n = 3) increase in IP3 formation that was maximal at 1 min and thereafter declined to basal levels by 15-30 min ( Figure 2A). NKA displayed an EC50 of 125 ± 11 nM (n = 6) with maximal stimulation observed at 500 nM ( Figure 2B).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…[1251]NKA binding was displaced by NKA with an IC50 of 12.6 ± 1.6 nM (n = 3) and by naturally occurring neurokinins with the relative rank order of affinity NKA>NKB>SP (Figure 1). This rank order of displacement is consistent with radioligand binding to the NK-2 receptor subtype (Grandordy et al, 1988;Regoli et al, 1989 at 10-6 M stimulated a rapid 4.6 ± 0.6-fold (n = 3) increase in IP3 formation that was maximal at 1 min and thereafter declined to basal levels by 15-30 min ( Figure 2A). NKA displayed an EC50 of 125 ± 11 nM (n = 6) with maximal stimulation observed at 500 nM ( Figure 2B).…”
Section: Introductionsupporting
confidence: 86%
“…Another important regulator of phospholipases associated with arachidonic acid generation is PKC (Exton, 1990), and inhibition with staurosporine (1 jiM) suppressed substantially NKA- half-maximal effect observed at 1.4 ± 0.6 nM (n = 6) ( Figure 8A). (Grandordy et aL, 1988;Regoli et al, 1989). Moreover, NKA-stimulated IP3 generation in the CB/4 clone is consistent with similar observations in guinea pig trachea (Grandordy et al, 1988), whereas NK-2 receptor-mediated increases in de novo DNA synthesis has also been reported previously in thymocytes, smooth muscle cells, and skin fibroblasts (Nilsson etal., 1985;Soder and Hellstrom, 1989).…”
Section: Introductionsupporting
confidence: 82%
“…In agreement with previous studies at NK-2 receptors in rat colon [22] and rabbit pulmonary artery [4], the binding affinity of NKA(4-10) was decreased 100-fold by replacement of Met 10 with Nle (data not shown). However, while the binding affinity of [Nle 10 ]NKA(4-10) is lower, other studies in rabbit isolated pulmonary artery have shown that the selectivity of this compound for the NK-2 receptor is improved [4,23,24].…”
Section: Discussionmentioning
confidence: 83%
“…We have, in our laboratory, regarded the interaction of the peptide hormone with extracellular Ca 2 + as an additional factor that would modify the conformation of the lipid-bound hormone [26]. That the Ca 2 + -bound structure is biologically relevant has been demonstrated by our showing a correlation between the activities of GnRH analogs and their extent of interaction with A large number of the structure-activity studies on SP are based on measurements on chemically modified forms of the parent hormone [44][45][46]. However, such studies tend to be empirical and do not provide a clue to the bioactive (receptor-bound) conformation of SP.…”
Section: Discussionmentioning
confidence: 93%